150 SGLT2 inhibition in heart failure with a reduced ejection fraction: how many patients would benefit?. (4th June 2021) - Hooper, Jacquelyn; Shaw, Steven; Callan, Paul; Williams, Simon
Abstract : Introduction: Sodium-glucose co-transporter (SGLT2) inhibition has been shown to reduce the risk of cardiovascular death or hospitalisation in patients with heart failure with reduced ejection fraction (HFrEF) with or without type 2 diabetes mellitus (T2DM). Since publication of the DAPA-HF 1 and EMPEROR-HF 2 trials and UK NICE approval, 3 SGLT2 inhibitor prescription has been increasing for patients with HFrEF. Methods: Electronic medical records were examined for all patients reviewed in heart failure clinic (including virtual consultation) at Wythenshawe hospital, Manchester over a 4 week period (25/01/21 - 19/02/21). Data obtained was stratified according to NYHA class, LV ejection fraction (LVEF) and presence or absence of T2DM. Results: 232 patients with a diagnosis of heart failure had either face to face or virtual telephone review over the specified time period. Patient baseline characteristics were comparable to patients recruited into the DAPA-HF and EMPEROR-HF trials*. Mean age 67 years (ranging from 20-94 years). 68% were male. 25% had T2DM. 19% (n=45) were subsequently excluded from further analysis due to improvement in LVEF >40% (mean time since last echo 5.4 months) or heart failure with preserved ejection fraction, along with 84 patients who were asymptomatic (NYHA I). 122 patients met the eligibility criteria* for SGLT2 inhibition: of whom 93% were already established on standard HF treatment (the combination of a beta-blocker, an aldosternone antagonist or either an ACE inhibitor, or angiotensin II receptor blocker ± neprolysin inhibitor. 8% were continuing uptitration of their standard heart failure treatments. In those not on standard HF therapy, a contraindication for the absent therapy was recorded in 50% of cases. 24% (n=29) were already prescribed SGLT2 inhibitors. Of the 30% (n=37) of patients who had T2DM, 43% (n=16) were prescribed SGLT2 inhibitors, leaving over half without. Amongst the non-diabetic population of eligible patients (n=86), only 15% were taking SGLT2 inhibitors. Eligible patients taking SGLT2 inhibitors (n=29) were prescribed Dapagliflozin in 79.3% of cases, with Empagliflozin and Canagliflozin prescribed much less commonly (10.3% and 10.3% respectively). Of those in the SGLT2 cohort, Dapagliflozin was commenced at the most recent clinic appointment in 45% of cases indicating a rapid uptake in the prescription of these agents. Conclusion: In line with recent NICE guidance, the use of SGLT2 inhibition in the HFrEF population is beginning to increase. There is scope for optimisation in treatment. In our cohort of an unselected group of consecutive patients In heart failure, 122/232 (53%) patients were eligible for the treatment. Of the patients with T2DM, 57% were not yet treated with SGLT2 inhibitors. The proportion of non-diabetic eligible patients not treated with SGLT2 inhibition was predictably higher (85%). However, this figure is likely to fall significantly over the next year as awareness of this new treatment increases and local guidance includes this class of agent.Eligibility criteria* for SGLT2 inhibition included: LV ejection fraction <40%, symptomatic heart failure (NYHA II or above) and an eGFR >30. Those with type 1 diabetes and a history of recurrent UTI were not deemed as eligible. Conflict of Interest: No References: McMurray JJV, Solomon SD, Inzucchi SE, Kober L, Kosiborod MN, Martinez FA, Ponikowski P, Sabatine MS, Anand IS, Belohlavek J, et al . Dapagliflozin in patients with heart failure and reduced ejection fraction. N Engl J Med 2019;381 :1995–2008. doi: 10.1056/NEJMoa1911303 Packer M, Anker SD, Butler J, Filippatos G, Pocock SJ, Carson P, Januzzi J, Verma S, Tsutsui H, Brueckmann M, et al ; EMPEROR-Reduced Trial Investigators. Cardiovascular and renal outcomes with empagliflozin in heart failure. N Engl J Med 2020;383 :1413–1424. doi: 10.1056/NEJMoa2022190 National Institute for Health and Care Excellence NICE technology appraisal guidance TA679.